Sub-surface mechanical properties and sub-surface creep behavior of wood-plastic composites reinforced by organoclay - Yadav, Sumit Manohar; Kamal, Yusoh (De Gruyter, 2019)
Wood-plastic composites (WPC) were manufactured from polypropylene, wood flour, maleic anhydride grafted polypropylene and organoclay. The sub-surface mechanical properties and the sub-surface creep behavior of the organoclay-based WPC were examined by the nanoindentation technique. The results showed that the hardness, elastic modulus and creep resistance of the WPC enhanced with the loading of C20 organoclay. This enhancement was subject to the organoclay content and the dispersion of organoclay in the polymer matrix. The hardness, elastic modulus and creep resistance of WPC with 1 wt% organoclay content enhanced by approximately 36%, 41% and 17%, respectively, in contrast with WPC without organoclay. To study the impact of organoclay content on the creep performance of WPC, a viscoelastic model was actualized. The results demonstrated that the model was in good agreement with the experimental information. Reinforcement of organoclay prompts expansion in elastic deformation and instigates a higher initial displacement at the early stage of creep.